EMBRYONIC DEVELOPMENTAL ANOMALY IDENTIFICATION OF GIANT MIMI-MINTUNO (Tachupleus gigas) DURING ARTIFICIAL INCUBATION PERIOD IN THE VIAL BOTTLES - Ciptono Ciptono; Tri Harjana (Jurnal Sains Dasar, 2015)
This study aims to reveal the phenomenon of presence / absence of anomalies in the early development of Mimi-giant mintuno (Tachypleus gigas) during artificial incubation in the vial bottles. Samples 5 eggs are fertilized incorporated into transparent 50 bottles and vials each filled with clear sea water medium. Embryonic stages (instars) hatch, bottles marked, then dumped seawater medium was replaced with 4% formalin solution and glycerin amount of 5% by volume, up to ¾ of the total volume of the vial bottles. Standard stages of giant Mimi-mintuno embryonic normal development Mimi-mintuno according to Itow (1988). The description type of anomalies contained in the post-hatching embryo development. The observations are documented in the form of stereo-microphotograph. The results showed that there are forms anomalies: (a). Delayed development, the structure of the body is not perfect; (b). In observation of the embryo hatches, open shell and egg perivitelline membrane has been opened but delayed development, the structure of the body is not perfect; (c). Embryos after hatched perfectly, abnormalities of morphologic structure such as abnormal protrusion on the dorsal carapace part found. Keywords: Tachypleus gigas, artificially, incubation